2020
DOI: 10.1097/wnp.0000000000000795
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Presenting With Confusion: An Unusual but Suggestive Electroencephalography Pattern of Encephalitis

Abstract: At initial investigation physical examination, blood and cerebrospinal fluid tests were unremarkable and EEG showed synchronous bifrontal periodic discharges, an evocative pattern of encephalitis. Coronavirus disease 2019 was diagnosed later after fever onset. Isolated mild confusion may thus be an initial clinical picture of Coronavirus disease 2019 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Although CSF testing of biomarkers is not universally available, we identified 57 patients who had CSF biomarkers measured, 45 (79%) of whom had elevation of at least one CSF biomarker suggesting the presence of inflammation, axonal injury, gliosis and Alzheimer-type pathologic changes [10,24,25,30,31,98,111,119,128,135,136,149,157,165,182,191,205,215,217,227,231,236]. Interestingly, some of these patients had elevation of biomarkers in the CSF, but not the serum, which is similar to ICANS, the neurotoxicity that occurs after treatment with chimeric antigen receptor T-cell therapy [10,217,231].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CSF testing of biomarkers is not universally available, we identified 57 patients who had CSF biomarkers measured, 45 (79%) of whom had elevation of at least one CSF biomarker suggesting the presence of inflammation, axonal injury, gliosis and Alzheimer-type pathologic changes [10,24,25,30,31,98,111,119,128,135,136,149,157,165,182,191,205,215,217,227,231,236]. Interestingly, some of these patients had elevation of biomarkers in the CSF, but not the serum, which is similar to ICANS, the neurotoxicity that occurs after treatment with chimeric antigen receptor T-cell therapy [10,217,231].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate for axonal injury, the CSF was tested for 1) 14-3-3 in 9 patients with encephalopathy, 2) neurofilament light chain in 8 patients with encephalopathy and 3) phosphorylated neurofilament heavy chain in 1 patient with ophthalmoplegia [10,24,25,119,157,217]. There were 4/9 (44%) patients who were positive for 14-3-3 in the CSF, 1 of whom was negative on an initial lumbar puncture then positive when a second CSF sample was obtained [24,25]. All of the patients with 14-3-3 detected in the CSF also had SARS-CoV-2 antibodies in the CSF at a 1:10 dilution and 3/4 had SARS-CoV-2 antibodies detected in the CSF at 1:100 dilution, though they all had a CSF:serum SARS-CoV-2 IgG index <1, and 2/4 had an elevated albumin index [25].…”
Section: Other Csf Biomarkersmentioning
confidence: 99%
“…After review of the 117 publications, we identified 193 patients who met inclusion criteria 1,2,10–124 . There were 105/189 (56%) male patients 1,2,10–12,14,16,17,19,22,26,27,31,33,35,37–40,46,47,50,51,54,57–60,62,64–71, 75,76,79,81,82,84,85,87,89,91,93,95–97,99,101–105,107–109,113–120,124 . The median age was 56 (range 2–96) years old …”
Section: Resultsmentioning
confidence: 99%
“…There were 105/189 (56%) male patients 1,2,10–12,14,16,17,19,22,26,27,31,33,35,37–40,46,47,50,51,54,57–60,62,64–71, 75,76,79,81,82,84,85,87,89,91,93,95–97,99,101–105,107–109,113–120,124 . The median age was 56 (range 2–96) years old 1,2,10–122,124 . There were 79/167 (47%) patients with severe COVID‐19 …”
Section: Resultsmentioning
confidence: 99%
“…An early case report describes a 78 year old male patient whose main complaint at admission was acute confusion, behavioral disorders, and cognitive troubles 31 . The physical exam, blood and cerebral spinal fluid (CSF) tests were unremarkable.…”
Section: Case Reportsmentioning
confidence: 99%